The Contribution of CSR to the Global Performance of Companies: Caseof Moroccan companies with a CSR label - El KHORCHI, El KHORCHI hamdi; MAZZINE, MAZZINE mohammed (Revue du contrôle, de la comptabilité et de l’audit, 2023)
In order to ensure a sustainable development of their structures, the leaders of Moroccan companies are now aware of the need to take into account in their strategic policies new concepts that can meet the expectations of different stakeholders (consumers, employees, government, NGOs,) Based on the assumption that sustainable development and sustainability of companies are closely linked to CSR. The benefits of CSR are not limited to the financial and economic component, but they also involve a renewal of thinking on the objectives and operation of the company Morocco has been undergoing profound economic, social and environmental changes for several years now. Moreover, CSR has gradually become an important theme of globalization, which explains why, despite its voluntary and non-compulsory nature, companies are obliged to adhere to it, but the power to engage in CSR actions depends on the top management and governance bodies of the company. This is why, we have witnessed in recent years a strengthening of governance mechanisms, particularly at the legislative level and the rules of "good governance" enacted or proposed by various regulatory or professional bodies such as the OECD. A question arising from the commitment of companies in terms of CSR has taken on a crucial importance: the impact of CSR on the performance of companies and we seek to answer the relationship between CSR and corporate governance and the relationship between governance and performance.